Enhancing the Anti-Fouling Property of Polyethersulfone-based Membrane using Chitosan Additive from Golden Snail (Pomacea canaliculata) Shell Waste for Water Purification - Sri Mulyati; Cut Meurah Rosnelly; Yanna Syamsuddin; Nasrul Arahman; Syawaliah Muchtar; Wahyuni Wahyuni; Tiara Lauzia; Aulia Chintia Ambarita; Muhammad Roil Bilad; Shafirah Samsuri (ASEAN Journal of Chemical Engineering, 2023)
One of the common techniques for treating water and water from waste effluent is membrane filtration. Polymer is the main material that is most extensively employed as a substance for membranes. Because of its outstanding strength and resistance to chemicals, Polyethersulfone, also known as PES, is a common polymer used in the production of membranes. Unfortunately, its hydrophobicity makes it easy to foul when applied to water treatment processes. This study introduced a chitosan additive isolated from golden snail shell waste as an additive for PES-based membrane fabrication via blending at 0 wt%, 1 wt%, 3 wt%, 5 wt%, and 7 wt%. After preparation, the resultant membranes were analyzed and tested for their ability to filter a humic acid solution at a concentration of 50 mg L-1. According to the findings, the chitosan additive has the potential to change the characteristics of the membrane as well as its filtration performance. It increased the pure water flux from 110 181 L m-2 h-1 (no chitosan loading) to 181 L m-2 h-1 (for five wt% loadings). The membrane characterization results supported this increase in pure water flux, which showed that adding chitosan additives improved the porosity, size of pores, and hydrophilicity. The addition of this additive also has a good effect on the anti-fouling property by increasing the fouling recovery ratio (FRR). The FRRs for the modified membranes were 79% to 82%, which were higher than the neat PES membrane with an FRR of merely 60%.